2019
DOI: 10.3390/rs11131528
|View full text |Cite
|
Sign up to set email alerts
|

Towards Global Volcano Monitoring Using Multisensor Sentinel Missions and Artificial Intelligence: The MOUNTS Monitoring System

Abstract: Most of the world’s 1500 active volcanoes are not instrumentally monitored, resulting in deadly eruptions which can occur without observation of precursory activity. The new Sentinel missions are now providing freely available imagery with unprecedented spatial and temporal resolutions, with payloads allowing for a comprehensive monitoring of volcanic hazards. We here present the volcano monitoring platform MOUNTS (Monitoring Unrest from Space), which aims for global monitoring, using multisensor satellite-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 93 publications
(86 reference statements)
2
101
0
Order By: Relevance
“…For these reasons, SAR-based change detection (SAR-CD) was developed over many years to provide useful and reliable information on land surface changes that occur across different temporal and spatial scales (Bovolo and Bruzzone, 2005). SAR-CD usually finds different domain of application, and in particular for all concerns natural hazard related to floods , volcanoes (Bignami et al, 2013;Valade et al, 2019), earthquakes (Pierdicca et al, 2018), and tsunamis (Chini et al, 2008). SAR-CD algorithms typically generates the difference image and then classifies it, which consists of a binary classification problem, aiming at separating the change and the no change classes (hereafter CC and NCC) (Ajadi et al, 2016).…”
Section: Sar Data Exploitationmentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, SAR-based change detection (SAR-CD) was developed over many years to provide useful and reliable information on land surface changes that occur across different temporal and spatial scales (Bovolo and Bruzzone, 2005). SAR-CD usually finds different domain of application, and in particular for all concerns natural hazard related to floods , volcanoes (Bignami et al, 2013;Valade et al, 2019), earthquakes (Pierdicca et al, 2018), and tsunamis (Chini et al, 2008). SAR-CD algorithms typically generates the difference image and then classifies it, which consists of a binary classification problem, aiming at separating the change and the no change classes (hereafter CC and NCC) (Ajadi et al, 2016).…”
Section: Sar Data Exploitationmentioning
confidence: 99%
“…This quantity is mostly influenced by the phase difference between radar returns, a distinctive parameter measured by a coherent sensor such as SAR, and it is particularly related to the spatial arrangement of the scatterers within the pixel and thus to their possible random displacements. Its high sensitivity to surface changes is welldocumented and enables the detection of damages caused by catastrophic events such as volcano eruptions, earthquakes, and floods (e.g., Hoffmann, 2007;Chini et al, 2012;Valade et al, 2019). Compared to the SAR intensity, the coherence sensitivity to surface changes is much higher, because even a target rotation can create a temporal decorrelation, while to detect changes in the intensity, it is necessary that the roughness and the dielectric properties of surface change.…”
Section: Sar Data Exploitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquisition of satellite images and data for volcanological applications is continuously and rapidly growing (Ramsey and Harris, 2013;Furtney et al, 2018;Pritchard et al, unpublished), so that big data analysis techniques (i.e., artificial intelligence and machine learning) are progressively used for research purposes and for monitoring activity (Piscini and Lombardo, 2014;Anantrasirichai et al, 2018;Valade et al, 2019). In particular, with the advent of the new millenium, and with the development of internet, the dissemination and sharing of satellite data/products can be considered a pillar of open science in volcanology, also thanks to the growing availability of open data by space agencies (Delgado et al, 2019).…”
mentioning
confidence: 99%
“…Recent scientific pilot projects, as the European Volcano Observatory Space Services, EVOSS (Tait and Ferrucci, 2013) and the Committee on Earth Observation Satellite (CEOS) Volcano Pilot Project (Delgado et al, 2019), demonstrated the potential of integrating these space-based data for forecasting eruptions (Furtney et al, 2018), stressing the need to develop a volcanic monitoring system to support volcano observatories (Pritchard et al, unpublished). The Monitoring Unrest From Space (MOUNTS) project 1 , although in an embryonic stage, can be considered a first prototype of such integrated system, since it includes near-real time multi-parametric analysis (UV, IR and microwaves) derived from the ESA Sentinel constellation, at several volcanoes (Valade et al, 2019). However, apart from this example, a comprehensive integration of space-based datasets into an operational system for global volcano monitoring is at this time only envisioned, with several distinct groups working on a single RSO (deformation, degassing, ash, thermal;Reath et al, 2019a).…”
mentioning
confidence: 99%